e-PORTFOLIO AS OLEA TO IDENTIFY HIGHER ABILITY FOR STUDENTS IN HIGHER EDUCATION - Nasrullah Pemu (IAIN Ambon, 2022)
The importance of high ability (HA) for students in higher education so that they show ability as a resource who is ready to face the challenges in today's competitive era. This research was conducted to identify HA by utilizing online learning environment activities (OLEA). OLEA is applied in the form of online lecture activities combined with the e-portfolio approach. This activity involved 32 people who came from students majoring in mathematics class C 2019. By using a questionnaire distributed via Google Form, the results were analyzed using descriptive statistics. The results show that 1) the HA identification method with OLEA is good for motivating students to recognize their abilities, 2) OLEA needs to be designed in such a way as to initiate the development of students' HA, 3) the e-Portfolio approach is a good alternative to support OLEA.